Pre-lithiated negative pole piece, preparation method of lithium supplementing composite layer, lithium supplementing method, secondary battery and electronic device
By forming a lithium supplement layer and an interface layer on the negative electrode sheet of the lithium-ion battery, the problems of low efficiency and poor cycle life of the negative electrode material of the lithium-ion battery are solved, and higher energy density and lower cycle capacity attenuation are achieved.
Patent Information
- Application Number
- CN202510111748.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-01-23
AI Technical Summary
The first time the Coulombic material of existing lithium-ion battery negative electrode materials is low in efficiency and poor cycle life, making it difficult to meet the need to improve energy density.
By using the prelithiated negative electrode sheet and lithium supplement composite layer, the lithium supplement layer and the interface layer are formed on the negative electrode sheet, the conduction ability of lithium ions and the electron transfer efficiency are improved.
The first Coulomb efficiency of the secondary battery is improved, the cycle capacity attenuation is reduced, and the energy density of the battery is improved.
Smart Images

Figure CN119920905A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a pre-lithiated negative electrode plate, a preparation method of a lithium replenishing composite layer, a lithium replenishing method, a secondary battery and an electronic device. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, high power, and long cycle life. They are widely used in consumer electronics, electric bicycles, and electric vehicles. As their application scope continues to expand, the energy density and cycle performance requirements of lithium-ion batteries continue to increase. The current common lithium-ion battery negative electrode graphite material can no longer meet the requirements for energy density. Due to the high theoretical specific capacity of silicon-carbon or silicon-oxygen negative electrode materials, they can be used as ideal materials to improve the energy density of lithium-ion batteries. However, they have problems such as low first coulomb efficiency and poor cycle life.
[0003] In order to improve the initial coulombic efficiency of the negative electrode active material and reduce the cycle attenuation, the existing method is to pre-replenish lithium to the negative electrode plate to replenish the irreversible capacity consumed in the initial charge, discharge and cycle, improve the initial coulombic efficiency of the lithium-ion battery, and then improve the energy density of the lithium-ion battery. When the negative electrode active material is a mixture of silicon-carbon or silicon-oxygen negative electrode material and graphite material, the lithium replenishment efficiency of different negative electrode active materials is different, the amount of lithium replenishment in the same time is different, and the initial coulombic efficiency of different negative electrode active materials is different, which will affect the initial coulombic efficiency of the lithium-ion battery, and then affect the improvement of energy density. Summary of the invention
[0004] The purpose of this application is to provide a pre-lithiated negative electrode plate, a preparation method of a lithium replenishing composite layer, a lithium replenishing method, a secondary battery and an electronic device to improve the initial coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. The specific technical solution is as follows:
[0005] The first aspect of the present application provides a method for preparing a lithium supplement composite layer, which comprises the following steps:
[0006] (1) coating a lithium metal powder slurry on a support layer, drying it, and rolling it to form a lithium supplement layer; or rolling a lithium foil and / or a lithium alloy foil onto a support layer to form a lithium supplement layer; or coating a lithium or lithium alloy molten slurry on a support layer, cooling it, and rolling it to form a lithium supplement layer; wherein the rolling pressure P1 is 0.2T / 10mm to 1.8T / 10mm;
[0007] (2) coating the interface particles on the surface of the lithium replenishing layer to form an interface layer, and then rolling, the roller pressure P2 is 0.2T / 10mm to 1.8T / 10mm, preferably, the roller pressure P2 is 0.2T / 10mm to 0.8T / 10mm; the rolling temperature T1 is 20°C to 180°C, preferably, the rolling temperature T1 is 50°C to 120°C; the rolling standing time t1 is 5min to 60min, preferably, the rolling standing time t1 is 10min to 30min, to form a lithium replenishing composite layer.
[0008] The above method is used to prepare a lithium-replenishing composite layer, and then the negative electrode plate is pre-lithiated to obtain a pre-lithiated negative electrode plate. In the above pre-lithiated negative electrode plate, the second negative electrode active material and the first negative electrode active material both have a high lithium replenishment amount, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.
[0009] In one embodiment of the present application, the lithium replenishing composite layer includes a supporting layer, a lithium replenishing layer and an interface layer, wherein the lithium replenishing layer is arranged between the supporting layer and the interface layer; the interface layer includes interface particles, wherein the interface particles include at least one of a conductive agent or a lithium intercalation material, wherein the conductive agent includes at least one of conductive carbon black, carbon fiber, graphene or carbon nanotubes, and the lithium intercalation material includes at least one of artificial graphite, natural graphite, hard carbon, silicon-carbon material, silicon-oxygen material, lithium titanate, tin or tin-copper alloy; and the lithium replenishing layer includes at least one of lithium foil or lithium alloy foil. The lithium replenishing composite layer satisfies the above structure, and by selecting the above interface particles, the interface layer can have better electron and ion conductivity, and in the pre-lithiation process, it is beneficial for electrons and lithium ions to be transferred to the surface or the inside of the second negative electrode material layer and the first negative electrode material layer through the interface layer more quickly, which is beneficial for further replenishing lithium to the negative electrode plate, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0010] In one embodiment of the present application, the interface particles include a lithium-embedded material and a conductive agent, and based on the mass of the interface particles, the mass percentage of the lithium-embedded material is 80% to 99%, and the mass percentage of the conductive agent is 1% to 20%. When the interface particles include a lithium-embedded material and a conductive agent, and the mass percentages of the lithium-embedded material and the conductive agent are within the scope of the present application, the electron and ion conductivity of the interface layer can be further improved, and during the pre-lithiation process, it is beneficial for electrons and lithium ions to be more quickly transferred through the interface layer to the surface or interior of the second negative electrode material layer and the first negative electrode material layer, which is beneficial for further replenishing lithium to the negative electrode plate, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0011] In one embodiment of the present application, the thickness of the interface layer is 0.1 μm to 50 μm, and preferably, the thickness of the interface layer is 1 μm to 20 μm.
[0012] In one embodiment of the present application, the thickness of the lithium replenishing layer is 0.001 mm to 1 mm, and preferably, the thickness of the lithium replenishing layer is 0.005 mm to 0.1 mm.
[0013] In one embodiment of the present application, the support layer includes at least one of metal foil, polyethylene terephthalate film, polypropylene film, polyethylene film or polyimide film, and the metal foil includes copper foil, nickel foil, steel foil or copper-nickel alloy foil.
[0014] In one embodiment of the present application, along the running direction of the lithium-replenishing composite layer, the tensile strength of the support layer is 0.5N / 10mm to 200N / 10mm, preferably, the tensile strength of the support layer is 1N / 10mm to 100N / 10mm.
[0015] In one embodiment of the present application, the thickness of the support layer is 3 μm to 50 μm, and preferably, the thickness of the support layer is 5 μm to 20 μm.
[0016] The second aspect of the present application provides a lithium supplementation method, which comprises the following steps:
[0017] The negative electrode plate is dried, and the negative electrode plate includes a negative electrode current collector, a first negative electrode material layer and a second negative electrode material layer. Along the thickness direction of the negative electrode plate, the first negative electrode material layer is arranged between the negative electrode current collector and the second negative electrode material layer, and the second negative electrode material layer includes a silicon-containing substance; based on the mass of the first negative electrode material layer, the mass percentage of silicon element in the first negative electrode material layer is WSi1%, based on the mass of the second negative electrode material layer, the mass percentage of silicon element in the second negative electrode material layer is WSi2%, and WSi2>WSi1. The lithium-replenishing composite layer prepared by the preparation method in any of the above embodiments and the negative electrode plate are laminated so that the interface layer contacts the second negative electrode material layer, and a pre-lithiation treatment is performed. After the pre-lithiation treatment is completed, the lithium-replenishing composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.
[0018] The pre-lithiated negative electrode plate is prepared by the lithium replenishment method provided in the present application. In the above-mentioned pre-lithiated negative electrode plate, the second negative electrode active material and the first negative electrode active material both have a high lithium replenishment amount, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.
[0019] In one embodiment of the present application, during the pre-lithiation treatment, the interface pressure P3 between the interface layer and the second negative electrode material layer is 0.1MPa to 2MPa, preferably, the interface pressure P3 between the interface layer and the second negative electrode material layer is 0.2MPa to 1.0MPa; the bonding time t2 between the interface layer and the second negative electrode material layer is 0.5h to 72h, preferably, the bonding time t2 between the interface layer and the second negative electrode material layer is 1h to 48h, and the bonding temperature T2 between the interface layer and the second negative electrode material layer is 50℃ to 180℃, preferably, the bonding temperature T2 between the interface layer and the second negative electrode material layer is 60℃ to 160℃. By regulating the interface pressure, bonding time, and bonding temperature within the scope of the present application, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0020] The third aspect of the present application provides a pre-lithiated negative electrode sheet prepared according to the lithium replenishment method in any of the aforementioned embodiments, the negative electrode sheet includes a negative current collector, a third negative electrode material layer and a fourth negative electrode material layer, along the thickness direction of the negative electrode sheet, the third negative electrode material layer is arranged between the negative current collector and the fourth negative electrode material layer, the third negative electrode material layer includes a first negative electrode active material, the fourth negative electrode material layer includes a second negative electrode active material, and the second negative electrode active material includes a silicon-containing substance. Based on the mass of the third negative electrode material layer, the mass percentage of silicon in the third negative electrode material layer is WSi3%, based on the mass of the fourth negative electrode material layer, the mass percentage of silicon in the fourth negative electrode material layer is WSi4%, and the mass percentage of lithium in the fourth negative electrode material layer is WLi4%, WSi4>WSi3, 1.5%≤WLi4 / WSi4≤44.4%. Applying the above-mentioned pre-lithiated negative electrode sheet to a secondary battery can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. At the same time, the fourth negative electrode material layer includes silicon-containing substances, which is also beneficial to improving the kinetic performance of the secondary battery.
[0021] In one embodiment of the present application, based on the mass of the third negative electrode material layer, the mass percentage of lithium in the third negative electrode material layer is WLi3%, 1.1≤WLi4 / WLi3≤4.8, preferably, 1.4≤WLi4 / WLi3≤3.3; 0.2≤WLi4≤4.4. The value of the mass percentage of lithium in the fourth negative electrode material layer and its ratio to the mass percentage of lithium in the third negative electrode material layer are within the scope of the present application, and the second negative electrode active material and the first negative electrode active material both have a high amount of lithium supplementation, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0022] In one embodiment of the present application, 0.9≤WSi4≤43.5. The negative electrode sheet satisfies the above structure, the mass percentage of silicon element in the fourth negative electrode material layer is within the scope of the present application, and the second negative electrode active material has a high lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0023] In one embodiment of the present application, based on the mass of the second negative electrode active material, the mass percentage of the silicon-containing substance is S2%, 2≤S2≤100. The negative electrode plate satisfies the above structure, the mass percentage of the silicon-containing substance in the second negative electrode active material is within the scope of the present application, and the second negative electrode active material has a higher lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0024] In one embodiment of the present application, based on the mass of the third negative electrode material layer, the mass percentage of the first negative electrode active material is H1%, based on the mass of the fourth negative electrode material layer, the mass percentage of the second negative electrode active material is H2%, 0.1≤H2-H1≤10, preferably, 1≤H2-H1≤5. The difference between the mass percentage of the second negative electrode active material and the mass percentage of the first negative electrode active material is within the scope of the present application, the mass percentage of the second negative electrode active material matches the mass percentage of the first negative electrode active material, the mass percentage of the silicon element and the lithium element in different negative electrode material layers can be regulated, so that the second negative electrode active material and the first negative electrode active material both have a higher lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0025] In one embodiment of the present application, the surface density of the third negative electrode material layer is CW3 mg / cm 2 The surface density of the fourth negative electrode material layer is CW4 mg / cm 2 , 0.8≤CW3≤50, preferably, 1.0≤CW3≤13.0; 0.25≤CW4 / CW3≤1. The ratio of the surface density of the third negative electrode material layer, the surface density of the fourth negative electrode material layer and the surface density of the third negative electrode material layer is within the scope of the present application, and the surface density of the third negative electrode material layer matches the surface density of the fourth negative electrode material layer, so that the second negative electrode active material and the first negative electrode active material both have a high lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0026] In one embodiment of the present application, the silicon-containing material includes at least one of a silicon-carbon material or a silicon-oxygen material. The negative electrode sheet satisfies the above structure, and the use of the above silicon-containing material can make the second negative electrode active material have a higher lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0027] The fourth aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.
[0028] The fifth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.
[0029] Beneficial effects of this application:
[0030] The present application provides a pre-lithiated negative electrode plate, a preparation method of a lithium replenishing composite layer, a lithium replenishing method, a secondary battery and an electronic device. The pre-lithiated negative electrode plate includes a negative electrode current collector, a third negative electrode material layer and a fourth negative electrode material layer. Along the thickness direction of the negative electrode plate, the third negative electrode material layer is arranged between the negative electrode current collector and the fourth negative electrode material layer. The third negative electrode material layer includes a first negative electrode active material, and the fourth negative electrode material layer includes a second negative electrode active material. The second negative electrode active material includes a silicon-containing substance. Based on the mass of the third negative electrode material layer, the mass percentage of silicon in the third negative electrode material layer is WSi3%, based on the mass of the fourth negative electrode material layer, the mass percentage of silicon in the fourth negative electrode material layer is WSi4%, and the mass percentage of lithium in the fourth negative electrode material layer is WLi4%, WSi4>WSi3, 1.5%≤WLi4 / WSi4≤44.4%. The pre-lithiated negative electrode plate meets the above characteristics, can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.
[0031] Of course, implementing any product or method of the present application does not necessarily require achieving all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0033] Figure 1 A schematic diagram of the structure of a lithium-replenishing composite layer according to an embodiment of the present application;
[0034] Figure 2 A schematic diagram of the structure of a negative electrode plate and a lithium supplement composite layer during a pre-lithiation process of an implementation scheme of the present application;
[0035] Figure 3 A schematic diagram of the structure of a pre-lithiated negative electrode plate according to an implementation scheme of the present application. DETAILED DESCRIPTION
[0036] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application.
[0037] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0038] The first aspect of the present application provides a method for preparing a lithium supplement composite layer, which comprises the following steps:
[0039] (1) Under the condition of ambient temperature ≤30°C and humidity ≤1.7%, a lithium metal powder slurry is applied to a support layer and dried and rolled to form a lithium supplement layer; or a lithium foil and / or a lithium alloy foil is rolled to a support layer to form a lithium supplement layer; or a lithium or lithium alloy molten slurry is applied to a support layer and cooled and rolled to form a lithium supplement layer; wherein the roller pressure P1 is 0.2T / 10mm to 1.8T / 10mm; specifically, the roller pressure P11 of rolling after applying the lithium metal powder slurry to the support layer is 0.2T / 10mm to 1.8T / 10mm; the roller pressure P12 of rolling after rolling the lithium foil and / or the lithium alloy foil to the support layer is 0.2T / 10mm to 1.8T / 10mm; the roller pressure P13 of rolling after applying the lithium or lithium alloy molten slurry to the support layer is 0.2T / 10mm to 1.8T / 10mm;
[0040] (2) Under the condition of ambient temperature ≤30°C and humidity ≤1.7%, the interface particles are coated on the surface of the lithium replenishing layer to form an interface layer, and then roller pressing is performed, the roller pressure P2 is 0.2T / 10mm to 1.8T / 10mm, preferably, the roller pressure P2 is 0.2T / 10mm to 0.8T / 10mm; the roller pressing temperature T1 is 20°C to 180°C, preferably, the roller pressing temperature T1 is 50°C to 120°C; the roller pressing standing time t1 is 5min to 60min, preferably, the roller pressing standing time t1 is 10min to 30min, to form a lithium replenishing composite layer.
[0041] The inventors have found that the lithium-replenishing composite layer can be prepared by using the preparation method of the lithium-replenishing composite layer provided in the present application. Figure 1 As shown, the lithium supplement composite layer 10 includes a support layer 11, a lithium supplement layer 12 and an interface layer 13. The lithium supplement layer 12 is arranged between the support layer 11 and the interface layer 13. The interface layer has the ability to conduct electrons and ions. Take the above-mentioned negative electrode sheet that has not been pre-lithiated, such as Figure 2 As shown, the interface layer 13 is brought into contact with the second negative electrode material layer 16, the lithium supplement layer 12 and the second negative electrode material layer 16 form an internal short circuit, the lithium atoms in the lithium supplement layer 12 undergo an oxidation reaction to lose electrons to generate lithium ions, the electrons and lithium ions are first transferred to the surface or the inside of the second negative electrode material layer 16 through the interface layer 13, and then transferred to the surface or the inside of the first negative electrode material layer 15, the electrons and lithium ions undergo a reduction reaction in the first negative electrode material layer 15 and the second negative electrode material layer 16 to form a lithium intercalation compound, and the pre-lithiation process of the first negative electrode material layer 15 and the second negative electrode material layer 16 is realized. Since an interface layer is provided between the lithium supplement layer and the second negative electrode material layer, the possibility of the lithium supplement layer adhering to the surface of the second negative electrode material layer can be reduced, thereby reducing the side reactions that may occur due to the high activity of lithium metal in the lithium supplement layer, thereby reducing the impact on the electrochemical performance of the secondary battery. After the pre-lithiation treatment is completed, the lithium supplement composite layer and the negative electrode plate are peeled off to obtain a pre-lithiation negative electrode plate. The above stripping process can reduce the influence of the lithium metal single substance in the lithium replenishment layer on the electrochemical performance of the secondary battery after the lithium metal single substance remains on the surface of the second negative electrode material layer and enters the secondary battery, and the side reaction occurs. The lithium replenishment composite layer is prepared by the above method, and then the negative electrode plate is pre-lithiated to obtain a pre-lithiated negative electrode plate. In the above pre-lithiated negative electrode plate, the second negative electrode active material and the first negative electrode active material have a high lithium replenishment amount, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.
[0042] Exemplarily, P11 may be 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, or a range consisting of any two of the above values. P12 may be 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, or a range consisting of any two of the above values. P13 can be 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, or a range consisting of any two of the above values. P2 can be 0.2T / 10mm, 0.4T / 10mm, 0.6T / 10mm, 0.8T / 10mm, 1T / 10mm, 1.2T / 10mm, 1.4T / 10mm, 1.6T / 10mm, 1.8T / 10mm, or a range consisting of any two of the above values. T1 can be 20°C, 40°C, 50°C, 60°C, 80°C, 100°C, 120°C, 140°C, 160°C, 180°C, or a range consisting of any two of the above values. t1 can be 5 min, 9 min, 10 min, 15 min, 19 min, 20 min, 25 min, 29 min, 30 min, 35 min, 39 min, 40 min, 45 min, 49 min, 50 min, 55 min, 59 min, 60 min or a range consisting of any two of the above values.
[0043] In the present application, the lithium replenishing layer can be formed by coating and rolling a lithium metal powder slurry, or by rolling a lithium foil and / or a lithium alloy foil onto a support layer to form a lithium replenishing layer, or by coating a lithium or lithium alloy molten slurry onto a support layer and cooling and rolling to form a lithium replenishing layer. In the present application, the lithium alloy foil may include but is not limited to lithium aluminum alloy, and the lithium alloy in the lithium alloy molten slurry may include but is not limited to lithium aluminum alloy. Roller pressure refers to the force generated by two cylindrical rollers placed in parallel to control the pressure between the roller gap and the upper and lower rollers to apply pressure to the sample passing through the roller gap. The present application does not particularly limit the coating method of the interface particles on the surface of the lithium replenishing layer, as long as the purpose of the present application can be achieved. For example, the interface particles can be coated on the surface of the lithium replenishing layer by electrostatic spraying, roller coating or wiping.
[0044] In one embodiment of the present application, the lithium-replenishing composite layer includes a supporting layer, a lithium-replenishing layer and an interface layer, wherein the lithium-replenishing layer is disposed between the supporting layer and the interface layer; the interface layer includes interface particles, wherein the interface particles include at least one of a conductive agent or a lithium-intercalating material, wherein the conductive agent includes at least one of conductive carbon black, carbon fiber, graphene or carbon nanotubes, and the lithium-intercalating material includes at least one of artificial graphite, natural graphite, hard carbon, silicon-carbon material, silicon-oxygen material, lithium titanate, tin or tin-copper alloy; the lithium-replenishing layer includes at least one of lithium foil or lithium alloy foil. In the present application, the conductive carbon black may include but is not limited to at least one of Super P, acetylene black or Ketjen black; the carbon fiber may include but is not limited to at least one of vapor-grown carbon fiber (VGCF) or nanocarbon fiber; the carbon nanotube may include but is not limited to at least one of single-walled carbon nanotube, multi-walled carbon nanotube or few-walled carbon nanotube. The lithium replenishing composite layer satisfies the above structure. By selecting the above interface particles, the interface layer can have better electron and ion conductivity. During the pre-lithiation process, it is beneficial for electrons and lithium ions to be transferred to the surface or interior of the second negative electrode material layer and the first negative electrode material layer through the interface layer more quickly, which is beneficial for further replenishing lithium to the negative electrode plate, and can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0045] In one embodiment of the present application, the interface particles include a lithium intercalation material and a conductive agent, and based on the mass of the interface particles, the mass percentage of the lithium intercalation material is 80% to 99%, and the mass percentage of the conductive agent is 1% to 20%. Exemplarily, based on the mass of the interface particles, the mass percentage of the lithium intercalation material can be 80%, 81%, 83%, 85%, 87%, 89%, 90%, 91%, 93%, 95%, 97%, 99% or a range consisting of any two of the above values, and the mass percentage of the conductive agent can be 1%, 3%, 5%, 7%, 9%, 10%, 11%, 13%, 15%, 17%, 19%, 20% or a range consisting of any two of the above values. When the interface particles include lithium-embedded materials and conductive agents, and the mass percentage of the lithium-embedded materials and the conductive agents is within the scope of the present application, the electron and ion conductivity of the interface layer can be further improved. During the pre-lithiation process, it is beneficial for electrons and lithium ions to be transferred more quickly through the interface layer to the surface or interior of the second negative electrode material layer and the first negative electrode material layer, which is beneficial for further lithium replenishment of the negative electrode plate, and can further improve the initial coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0046] In one embodiment of the present application, the thickness of the interface layer is 0.1 μm to 50 μm, preferably, the thickness of the interface layer is 1 μm to 20 μm. Exemplarily, the thickness of the interface layer can be 0.1, 0.5, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range consisting of any two of the above values.
[0047] In one embodiment of the present application, the thickness of the lithium supplement layer is 0.001 mm to 1 mm, preferably, the thickness of the lithium supplement layer is 0.005 mm to 0.1 mm. Exemplarily, the thickness of the lithium supplement layer can be 0.001, 0.003, 0.005, 0.007, 0.009, 0.01, 0.03, 0.05, 0.07, 0.09, 0.1, 0.3, 0.5, 0.7, 0.9, 1 or a range consisting of any two of the above values.
[0048] In one embodiment of the present application, the support layer includes at least one of metal foil, polyethylene terephthalate film, polypropylene film, polyethylene film or polyimide film, and the metal foil includes copper foil, nickel foil, steel foil or copper-nickel alloy foil.
[0049] In one embodiment of the present application, along the running direction of the lithium-replenishing composite layer, the tensile strength of the support layer is 0.5N / 10mm to 200N / 10mm. Preferably, the tensile strength of the support layer is 1N / 10mm to 100N / 10mm. Exemplarily, the tensile strength of the support layer can be 0.5N / 10mm, 1N / 10mm, 5N / 10mm, 10N / 10mm, 50N / 10mm, 100N / 10mm, 150N / 10mm, 200N / 10mm or a range consisting of any two of the above values.
[0050] In one embodiment of the present application, the thickness of the support layer is 3 μm to 50 μm, preferably, the thickness of the support layer is 5 μm to 20 μm, and illustratively, the thickness of the support layer can be 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or a range consisting of any two of the above values.
[0051] The second aspect of the present application provides a lithium supplementation method, which comprises the following steps:
[0052] The negative electrode plate is dried until the water content is ≤500ppm. The negative electrode plate includes a negative current collector, a first negative electrode material layer and a second negative electrode material layer. Along the thickness direction of the negative electrode plate, the first negative electrode material layer is arranged between the negative current collector and the second negative electrode material layer, and the second negative electrode material layer includes a silicon-containing substance; based on the mass of the first negative electrode material layer, the mass percentage of silicon element in the first negative electrode material layer is WSi1%, based on the mass of the second negative electrode material layer, the mass percentage of silicon element in the second negative electrode material layer is WSi2%, WSi2>WSi1. Under the conditions of ambient temperature of 25°C to 180°C and humidity of ≤1.7%, the lithium supplement composite layer prepared by the preparation method in any of the above embodiments and the negative electrode plate are laminated so that the interface layer contacts the second negative electrode material layer, and a pre-lithiation treatment is performed. After the pre-lithiation treatment is completed, the lithium supplement composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.
[0053] In the present application, the negative electrode sheet that has not been pre-lithiated includes a negative electrode current collector, a first negative electrode material layer and a second negative electrode material layer. The above-mentioned negative electrode sheet that has not been pre-lithiated is pre-lithiated to obtain a pre-lithiated negative electrode sheet. The pre-lithiated negative electrode sheet includes a negative electrode current collector, a third negative electrode material layer and a fourth negative electrode material layer. It can be understood that the first negative electrode material layer before the pre-lithiation treatment corresponds to the third negative electrode material layer after the pre-lithiation treatment, and the second negative electrode material layer before the pre-lithiation treatment corresponds to the fourth negative electrode material layer after the pre-lithiation treatment. The first negative electrode material layer includes a first negative electrode active material, and the second negative electrode material layer includes a second negative electrode active material.
[0054] The pre-lithiated negative electrode plate is prepared by the lithium replenishment method provided in the present application. In the above-mentioned pre-lithiated negative electrode plate, the second negative electrode active material and the first negative electrode active material both have a high lithium replenishment amount, which can improve the first coulombic efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery.
[0055] In one embodiment of the present application, during the pre-lithiation treatment, the interface pressure P3 between the interface layer and the second negative electrode material layer is 0.1MPa to 2MPa, preferably, the interface pressure P3 between the interface layer and the second negative electrode material layer is 0.2MPa to 1.0MPa; the bonding time t2 between the interface layer and the second negative electrode material layer is 0.5h to 72h, preferably, the bonding time t2 between the interface layer and the second negative electrode material layer is 1h to 48h, and the bonding temperature T2 between the interface layer and the second negative electrode material layer is 50℃ to 180℃, preferably, the bonding temperature T2 between the interface layer and the second negative electrode material layer is 60℃ to 160℃. By regulating the interface pressure, bonding time, and bonding temperature within the scope of the present application, the first coulombic efficiency of the secondary battery can be further improved, the cycle capacity attenuation can be further reduced, and the energy density of the secondary battery can be further improved.
[0056] For example, P3 can be 0.1MPa, 0.2MPa, 0.4MPa, 0.6MPa, 0.8MPa, 1.0MPa, 1.2MPa, 1.4MPa, 1.6MPa, 1.8MPa, 2MPa, or a range consisting of any two of the above values. t2 can be 0.5h, 1h, 5h, 10h, 15h, 20h, 25h, 30h, 35h, 40h, 45h, 48h, 50h, 55h, 60h, 65h, 70h, 72h, or a range consisting of any two of the above values. T2 can be 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, or a range consisting of any two of the above values.
[0057] The third aspect of the present application provides a pre-lithiated negative electrode sheet prepared by the lithium replenishment method in any of the aforementioned embodiments, such as Figure 3 As shown, the pre-lithiated negative electrode sheet includes a negative electrode current collector 14, a third negative electrode material layer 17 and a fourth negative electrode material layer 18. Along the thickness direction of the negative electrode sheet, that is, the Y direction, the third negative electrode material layer 17 is arranged between the negative electrode current collector 14 and the fourth negative electrode material layer 18. The third negative electrode material layer 17 includes a first negative electrode active material, and the fourth negative electrode material layer 18 includes a second negative electrode active material. The second negative electrode active material includes a silicon-containing substance. Based on the mass of the third negative electrode material layer, the mass percentage content of silicon element in the third negative electrode material layer is WSi3%, based on the mass of the fourth negative electrode material layer, the mass percentage content of silicon element in the fourth negative electrode material layer is WSi4%, and the mass percentage content of lithium element in the fourth negative electrode material layer is WLi4%, WSi4>WSi3, 1.5%≤WLi4 / WSi4≤44.4%. Exemplarily, the value of WLi4 / WSi4 can be 1.5%, 5%, 7%, 9%, 10%, 15%, 17%, 19%, 20%, 25%, 27%, 29%, 30%, 35%, 37%, 39%, 40%, 44.4% or a range consisting of any two of the above values. In the present application, the third negative electrode material layer and the fourth negative electrode material layer can be sequentially arranged on one surface of the negative electrode collector along its own thickness direction, or the third negative electrode material layer and the fourth negative electrode material layer can be sequentially arranged on two surfaces of the negative electrode collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the negative electrode collector or a partial area of the negative electrode collector. There is no special limitation in the present application as long as the purpose of the present application can be achieved. In some embodiments of the present application, WSi3=0.
[0058] The inventors have found that within the same pre-lithiation treatment period, different negative electrode active materials have different lithium replenishment efficiencies. The amount of lithium replenishment for silicon-containing materials is relatively small, while the amount of lithium replenishment for carbon materials is relatively large. Therefore, the first coulombic efficiency of silicon-containing materials will be affected. Take a negative electrode sheet that has not been pre-lithiated. The negative electrode sheet includes a negative electrode current collector, a first negative electrode material layer, and a second negative electrode material layer. Along the thickness direction of the negative electrode sheet, the first negative electrode material layer is arranged between the negative electrode current collector and the second negative electrode material layer. The second negative electrode material layer includes a silicon-containing material, the first negative electrode material layer does not include a silicon-containing material, and the first negative electrode material layer includes a carbon material. Pre-lithiation treatment is performed on the above-mentioned negative electrode sheet that has not been pre-lithiated, so that the silicon-containing material in the second negative electrode material layer can be replenished with lithium first, and then the carbon material in the first negative electrode material layer can be replenished with lithium to obtain a pre-lithiated negative electrode sheet. The negative electrode plate satisfies the above structure, and the mass percentage of the silicon-containing substance in different negative electrode material layers is within the scope of the present application, which is conducive to the directional lithium replenishment of the silicon-containing substance in the second negative electrode material layer, thereby improving the lithium replenishment efficiency of the silicon-containing substance. The pre-lithiated negative electrode plate includes a negative electrode current collector, a third negative electrode material layer and a fourth negative electrode material layer. Along the thickness direction of the negative electrode plate, the third negative electrode material layer is arranged between the negative electrode current collector and the fourth negative electrode material layer. The third negative electrode material layer includes a first negative electrode active material, and the fourth negative electrode material layer includes a second negative electrode active material. The second negative electrode active material includes a silicon-containing substance, and the first negative electrode active material does not include a silicon-containing substance. The first negative electrode active material includes a carbon material. The mass percentage of silicon in the fourth negative electrode material layer is greater than the mass percentage of silicon in the third negative electrode material layer, and the ratio of the mass percentage of lithium in the fourth negative electrode material layer to the mass percentage of silicon is within the scope of this application. The second negative electrode active material and the first negative electrode active material both have a high amount of lithium supplementation. The above-mentioned pre-lithiated negative electrode plate is applied to the secondary battery, which can improve the first coulomb efficiency of the secondary battery, reduce the cycle capacity attenuation, and improve the energy density of the secondary battery. At the same time, the fourth negative electrode material layer includes silicon-containing substances, which is also conducive to the improvement of the kinetic performance of the secondary battery.
[0059] In the present application, the carbon material includes at least one of artificial graphite, natural graphite, hard carbon, mesophase microcarbon beads (MCMB) or soft carbon.
[0060] In one embodiment of the present application, based on the mass of the third negative electrode material layer, the mass percentage of lithium element in the third negative electrode material layer is WLi3%, 1.1≤WLi4 / WLi3≤4.8, preferably, 1.4≤WLi4 / WLi3≤3.3, exemplarily, the value of WLi4 / WLi3 can be 1.1, 1.4, 1.5, 2.0, 2.5, 3.0, 3.3, 3.5, 4.0, 4.5, 4.8 or a range consisting of any two of the above values; 0.2≤WLi4≤4.4, exemplarily, the value of WLi4 can be 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, 1.8, 2, 2.2, 2.4, 2.6, 2.8, 3, 3.2, 3.4, 3.6, 3.8, 4, 4.2, 4.4 or a range consisting of any two of the above values. The value of the mass percentage of lithium element in the fourth negative electrode material layer and its ratio to the mass percentage of lithium element in the third negative electrode material layer are within the scope of this application, and the second negative electrode active material and the first negative electrode active material both have a high amount of lithium supplementation, which can further improve the initial coulombic efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery. In this application, 0.08≤WLi3≤0.92, illustratively, the value of WLi3 can be 0.08, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 0.92 or a range consisting of any two of the above values.
[0061] The present application has no particular restrictions on the method of regulating the mass percentage of silicon in the fourth negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the mass percentage of silicon in the fourth negative electrode material layer can be regulated by regulating the mass percentage of silicon-containing substances added to the fourth negative electrode material layer. The present application has no particular restrictions on the method of regulating the mass percentage of lithium in the third negative electrode material layer and the mass percentage of lithium in the fourth negative electrode material layer, as long as the purpose of the present application can be achieved. For example, the mass percentage of lithium in the third negative electrode material layer and the mass percentage of lithium in the fourth negative electrode material layer can be regulated by regulating the lamination time, lamination temperature or interface pressure of the pre-lithiation treatment process. The present application has no particular restrictions on the method of regulating WLi4 / WSi4, as long as the purpose of the present application can be achieved. For example, the value of WLi4 / WSi4 can be regulated by regulating the respective values of WLi4 and WSi4, and the regulation method is as described above. The present application has no particular restrictions on the method of regulating WLi4 / WLi3, as long as the purpose of the present application can be achieved. For example, the value of WLi4 / WLi3 may be adjusted by adjusting the respective values of WLi4 and WLi3, and the adjustment method is as described above.
[0062] In one embodiment of the present application, 0.9≤WSi4≤43.5, illustratively, the value of WSi4 can be 0.9, 1, 5, 10, 15, 20, 25, 30, 35, 40, 42, 43.5 or a range consisting of any two of the above values. The negative electrode sheet satisfies the above structure, the mass percentage of silicon element in the fourth negative electrode material layer is within the scope of the present application, and the second negative electrode active material has a higher lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0063] In one embodiment of the present application, based on the mass of the second negative electrode active material, the mass percentage of the silicon-containing substance is S2%, 2≤S2≤100. For example, the value of S2 can be 2, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100 or a range consisting of any two of the above values. The negative electrode plate satisfies the above structure, and the mass percentage of the silicon-containing substance in the second negative electrode active material is within the scope of the present application. The second negative electrode active material has a higher lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery. The present application does not particularly limit the method of regulating the mass percentage of the silicon-containing substance in the second negative electrode active material, as long as the purpose of the present application can be achieved. For example, the mass percentage of the silicon-containing substance in the second negative electrode active material can be regulated by regulating the mass percentage of the added silicon-containing substance.
[0064] In the present application, the second negative electrode active material may further include a carbon material. Based on the mass of the second negative electrode active material, the mass percentage of the carbon material is C2%, 0≤C2≤98, and illustratively, the value of C2 may be 0, 10, 20, 30, 40, 50, 60, 70, 80, 90, 98, or a range consisting of any two of the above values.
[0065] In one embodiment of the present application, based on the mass of the third negative electrode material layer, the mass percentage of the first negative electrode active material is H1%, based on the mass of the fourth negative electrode material layer, the mass percentage of the second negative electrode active material is H2%, 0.1≤H2-H1≤10, preferably, 1≤H2-H1≤5, illustratively, the value of H2-H1 can be 0.1, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5, 7, 7.5, 8, 8.5, 9, 9.5, 10 or a range consisting of any two of the above values. The difference between the mass percentage of the second negative electrode active material and the mass percentage of the first negative electrode active material is within the scope of this application, and the mass percentage of the second negative electrode active material matches the mass percentage of the first negative electrode active material, which can regulate the mass percentage of silicon and lithium in different negative electrode material layers, so that both the second negative electrode active material and the first negative electrode active material have a high amount of lithium supplement, which can further improve the initial coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery. In this application, 65≤H1≤98.9, 75≤H2≤99.
[0066] The present application has no particular restrictions on the method of regulating the mass percentage of the first negative electrode active material and the mass percentage of the second negative electrode active material, as long as the purpose of the present application can be achieved. For example, the mass percentage of the first negative electrode active material can be regulated by regulating the mass percentage of the added first negative electrode active material; the mass percentage of the second negative electrode active material can be regulated by regulating the mass percentage of the added second negative electrode active material. The present application has no particular restrictions on the method of regulating H2-H1, as long as the purpose of the present application can be achieved. For example, the value of H2-H1 can be regulated by regulating the respective values of H2 and H1, and the regulation method is as described above.
[0067] In one embodiment of the present application, the surface density of the third negative electrode material layer is CW3 mg / cm 2 The surface density of the fourth negative electrode material layer is CW4 mg / cm 2, 0.8≤CW3≤50, preferably, 1.0≤CW3≤13.0, exemplarily, the value of CW3 can be 0.8, 1, 3, 5, 7, 10, 13, 15, 17, 20, 23, 25, 27, 30, 33, 35, 37, 40, 43, 45, 47, 50 or a range consisting of any two of the above values; 0.25≤CW4 / CW3≤1, exemplarily, the value of CW4 / CW3 can be 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or a range consisting of any two of the above values. The ratio of the surface density of the third negative electrode material layer and the surface density of the fourth negative electrode material layer to the surface density of the third negative electrode material layer is within the scope of this application, and the surface density of the third negative electrode material layer matches the surface density of the fourth negative electrode material layer, so that the second negative electrode active material and the first negative electrode active material both have a high amount of lithium supplementation, which can further improve the initial coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery. In this application, 0.2≤CW4≤50.
[0068] The present application has no particular restrictions on the manner of regulating the surface density of the third negative electrode material layer and the fourth negative electrode material layer, as long as the purpose of the present application can be achieved. It can be understood that the surface density of the third negative electrode material layer is related to the surface density of the first negative electrode material layer, and the surface density of the third negative electrode material layer is the sum of the surface density of the first negative electrode material layer and the surface density of lithium supplementation; the surface density of the fourth negative electrode material layer is related to the surface density of the second negative electrode material layer, and the surface density of the fourth negative electrode material layer is the sum of the surface density of the second negative electrode material layer and the surface density of lithium supplementation. The surface density of the third negative electrode material layer can be regulated by regulating the surface density and / or the surface density of lithium supplementation of the first negative electrode material layer, and the surface density of the fourth negative electrode material layer can be regulated by regulating the surface density and / or the surface density of lithium supplementation of the second negative electrode material layer. For example, when the first negative electrode slurry is coated on the surface of the negative electrode current collector, on the basis of a certain solid content of the first negative electrode slurry, the coating amount of the first negative electrode slurry is increased to increase the surface density of the first negative electrode material layer; when the second negative electrode slurry is coated on the surface of the first negative electrode material layer, on the basis of a certain solid content of the second negative electrode slurry, the coating amount of the second negative electrode slurry is increased to increase the surface density of the second negative electrode material layer. For example, the surface density of lithium supplementation can be regulated by regulating the interface pressure, bonding time, and bonding temperature during the pre-lithiation treatment. The present application has no particular restrictions on the method of regulating CW4 / CW3, as long as the purpose of the present application can be achieved. For example, the value of CW4 / CW3 can be regulated by regulating the respective values of CW4 and CW3, and the regulation method is as described above.
[0069] In one embodiment of the present application, the silicon-containing material includes at least one of a silicon-carbon material or a silicon-oxygen material. In the present application, the silicon-carbon material is a silicon-carbon composite material, and based on the mass of the silicon-carbon composite material, the mass percentage of the silicon element is 30% to 70%, and the mass percentage of the carbon element is 30% to 70%. The present application has no particular restrictions on the silicon-carbon composite material, as long as the purpose of the present application can be achieved. For example, the silicon-carbon composite material can be a composite material obtained by deposition. Exemplarily, the silicon-carbon composite material can be a silicon material deposited on a carbon skeleton, or a carbon material deposited on a silicon skeleton. The silicon-oxygen material includes SiOx, where 0<x<2. Exemplarily, the silicon-oxygen material can include silicon oxide (SiO, the molar ratio of silicon to oxygen is 1:1). The negative electrode sheet satisfies the above structure, and the selection of the above silicon-containing material can enable the second negative electrode active material to have a higher lithium supplement amount, which can further improve the first coulomb efficiency of the secondary battery, further reduce the cycle capacity attenuation, and further improve the energy density of the secondary battery.
[0070] In the present application, the first negative electrode material layer also includes a negative electrode binder and a negative electrode conductor, and the second negative electrode material layer also includes a negative electrode binder and a negative electrode conductor. The present application does not particularly limit the type of negative electrode binder, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include polyacrylate, polyimide, polyamide, polyamide-imide, polyvinylidene fluoride, polystyrene butadiene copolymer (styrene-butadiene rubber, SBR), sodium alginate, polyvinyl alcohol, polytetrafluoroethylene, polyacrylonitrile, sodium carboxymethyl cellulose, potassium carboxymethyl cellulose, lithium carboxymethyl cellulose, lithium polyacrylate, sodium hydroxymethyl cellulose or potassium hydroxymethyl cellulose. The present application does not particularly limit the type of negative electrode conductor, as long as the purpose of the present application can be achieved. For example, the negative electrode conductor may include but is not limited to conductive carbon black, carbon nanotubes (CNTs), carbon fibers, flake graphite, graphene, metal materials or conductive polymers. The above-mentioned metal materials may include but are not limited to metal powders and / or metal fibers. Specifically, the metal may include but is not limited to at least one of copper, nickel, aluminum or silver. The above-mentioned conductive polymer may include but is not limited to at least one of polyphenylene derivatives, polyaniline, polythiophene, polyacetylene or polypyrrole. The present application has no particular restriction on the mass percentage of the negative electrode binder and the negative electrode conductive agent in the first negative electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved. The present application has no particular restriction on the mass percentage of the negative electrode binder and the negative electrode conductive agent in the second negative electrode material layer. Those skilled in the art can select according to actual needs as long as the purpose of the present application can be achieved.
[0071] The present application has no particular restrictions on the negative electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper or a composite current collector (such as a lithium-copper composite current collector, a carbon-copper composite current collector, a nickel-copper composite current collector, a titanium-copper composite current collector, etc.), etc.
[0072] The present application has no particular restrictions on the thickness of the negative electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the negative electrode current collector is 4 μm to 20 μm. The present application has no particular restrictions on the thickness of the first negative electrode material layer and the second negative electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided first negative electrode material layer is 8 μm to 265 μm; the thickness of the single-sided second negative electrode material layer is 2 μm to 265 μm.
[0073] The fourth aspect of the present application provides a secondary battery, which includes the pre-lithiated negative electrode plate in any of the above embodiments. Therefore, the secondary battery provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.
[0074] In the present application, the secondary battery also includes a positive electrode plate. The positive electrode plate includes a positive current collector and a positive electrode material layer disposed on at least one surface of the positive current collector. The above-mentioned "positive electrode material layer disposed on at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its own thickness direction, or on two surfaces of the positive current collector along its own thickness direction. It should be noted that the "surface" here can be the entire area of the positive current collector or a partial area of the positive current collector. This application is not particularly limited as long as the purpose of this application can be achieved.
[0075] The present application has no particular limitation on the positive electrode current collector, as long as the purpose of the present application can be achieved. For example, it may include aluminum foil, aluminum alloy foil or a composite current collector (such as an aluminum-carbon composite current collector).
[0076] The positive electrode material layer of the present application includes a positive electrode active material, and the positive electrode active material includes a substance that can reversibly embed and extract active ions such as lithium ions. The positive electrode material layer can be one layer or more layers, and each layer in the multi-layer positive electrode material layer can contain the same or different positive electrode active materials. The present application has no special restrictions on the positive electrode active material, as long as the purpose of the present application can be achieved. For example, the positive electrode active material may include but is not limited to lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium iron manganese phosphate or lithium titanate. At least one of the above-mentioned lithium nickel cobalt manganese oxide may include LiNi 0.95 Co 0.03 Mn 0.02 O2(Ni95),LiNi0.91 Co 0.03 Mn 0.06 O2(Ni91), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523) or LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 At least one of O2 (NCM111). The positive electrode material layer of the present application also includes a positive electrode conductor and a positive electrode binder. The present application has no special restrictions on the positive electrode conductor and the positive electrode binder, as long as the purpose of the present application can be achieved. For example, the positive electrode conductor may include at least one of the above-mentioned negative electrode conductors; the positive electrode binder may include at least one of the above-mentioned negative electrode binders. The present application has no special restrictions on the mass ratio of the positive electrode active material, the positive electrode conductor, and the positive electrode binder in the positive electrode material layer. Those skilled in the art can choose according to actual needs, as long as the purpose of the present application can be achieved.
[0077] The present application has no particular limitation on the thickness of the positive electrode current collector, as long as the purpose of the present application can be achieved, for example, the thickness of the positive electrode current collector is 6 μm to 25 μm. The present application has no particular limitation on the thickness of the positive electrode material layer, as long as the purpose of the present application can be achieved, for example, the thickness of the single-sided positive electrode material layer is 25 μm to 250 μm.
[0078] In the present application, the secondary battery also includes an electrolyte. The electrolyte includes a lithium salt. The present application has no particular restrictions on the type of lithium salt, and lithium salts known in the art can be used. For example, the lithium salt may include but is not limited to lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiN(CF3SO2)2, LiTFSI), lithium bis(fluorosulfonyl)imide (Li(N(SO2F)2), LiFSI), lithium difluorophosphate (LiPO2F2), lithium bis(oxalate borate) (LiB(C2O4)2, LiBOB) or lithium difluorooxalate borate (LiBF2(C2O4), LiDFOB). The present application has no particular restrictions on the mass percentage of lithium salt in the electrolyte, as long as the purpose of the present application can be achieved. The electrolyte also includes a non-aqueous organic solvent. The present application has no particular restrictions on the non-aqueous organic solvent, as long as the purpose of the present application can be achieved. For example, the non-aqueous organic solvent may contain at least one of a carbonate compound, a carboxylate compound, an ether compound or other organic solvents. The above-mentioned carbonate compound may include but is not limited to at least one of a linear carbonate compound, a cyclic carbonate compound or a fluorinated carbonate compound. The above-mentioned linear carbonate compound may include but is not limited to at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) or ethyl methyl carbonate (EMC). The above-mentioned cyclic carbonate compound may include but is not limited to at least one of ethylene carbonate (EC), vinylene carbonate, propylene carbonate (PC), butylene carbonate (BC) or vinyl ethylene carbonate (VEC). The above-mentioned fluorinated carbonate compound may include but is not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate. The above-mentioned carboxylate compound may include but is not limited to at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate or propyl propionate. The above-mentioned ether compound may include but is not limited to at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran. The above-mentioned other organic solvents may include, but are not limited to, at least one of 1,3-propanesultone, dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester.The present application has no particular limitation on the mass percentage of the non-aqueous organic solvent in the electrolyte, as long as the purpose of the present application can be achieved.
[0079] In the present application, the secondary battery also includes a diaphragm. The diaphragm is used to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm may include but is not limited to polyethylene (PE), polypropylene (PP)-based polyolefins (PO), polyesters (for example, polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex or aramid; the type of diaphragm may include at least one of a woven membrane, a non-woven membrane, a microporous membrane, a composite membrane, a rolled membrane or a spun membrane.
[0080] In the present application, the diaphragm may include a substrate and a surface treatment layer. The substrate may be a non-woven fabric or a composite film having a porous structure, and the material of the substrate may include at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Optionally, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate, and the surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. For example, the inorganic layer includes inorganic particles and a diaphragm binder, and the present application has no particular restrictions on the above-mentioned inorganic particles, for example, it may include at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. The present application has no particular restrictions on the above-mentioned diaphragm binder, for example, it may be at least one of the aforementioned negative electrode binders. The polymer layer contains a polymer, and the material of the polymer includes at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyvinyl pyrrolidone, polyvinyl ether, polyvinylidene fluoride or vinylidene fluoride-hexafluoropropylene copolymer.
[0081] The secondary battery of the present application also includes a packaging bag for containing a positive electrode plate, a separator, a pre-lithiated negative electrode plate and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application.
[0082] The present application does not particularly limit the type of secondary battery, which may include any device that undergoes an electrochemical reaction. In the present application, the secondary battery may include, but is not limited to: a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery or a lithium ion polymer secondary battery (lithium ion polymer battery), etc.
[0083] The preparation process of the secondary battery of the present application is well known to those skilled in the art, and the present application has no special restrictions. For example, it may include but is not limited to the following steps: stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and winding, folding and other operations as needed to obtain an electrode assembly of a winding structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the positive electrode sheet, the separator and the pre-lithiated negative electrode sheet in order, and then fixing the four corners of the entire stacked structure with tape to obtain an electrode assembly of a stacked structure, placing the electrode assembly in a packaging bag, injecting the electrolyte into the packaging bag and sealing it to obtain a secondary battery. In addition, overcurrent protection components, guide plates, etc. may also be placed in the packaging bag as needed to prevent the pressure inside the secondary battery from rising and overcharging and discharging.
[0084] The fifth aspect of the present application provides an electronic device, which includes the secondary battery in any of the above embodiments. Therefore, the electronic device provided by the present application has a higher first coulombic efficiency, lower cycle capacity decay and higher energy density.
[0085] The present application does not particularly limit the type of electronic device, which can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0086] Example
[0087] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0088] Test methods and equipment:
[0089] Mass percentage test of elements in the negative electrode material layer:
[0090] Take the pre-lithiated negative electrode sheet, cut it into 6mm×6mm size samples, and glue it to the sample table with conductive glue; then use a cross section polisher (model IB-19520CCP) to polish the sample cross section. The polishing conditions are: vacuum degree 10 -3 Pa, the acceleration voltage is 6kV, and the grinding speed is 500 microns / hour. The polished sample is placed on the sample stage of a scanning electron microscope, and its cross section is tested by a scanning electron microscope (SEM, Scanning electron microscope, model is Thermo Fisher FEI-Apreo S). The test conditions are: acceleration voltage is 10kV, grating is 10spot, working distance WD is 10mm, and magnification is 2000 times. The fourth negative electrode material layer contains irregular silicon particles, and the third negative electrode material layer does not contain irregular silicon particles. The thickness of the fourth negative electrode material layer at 10 positions is tested respectively, and the average value Thk4 is taken; the thickness of the third negative electrode material layer at 10 positions is tested respectively, and the average value Thk3 is taken.
[0091] Select the area including the double-sided negative electrode material layer on the pre-lithiation negative electrode plate, and cut 10 pieces with an area of 1540.25mm using a cutting machine. 2 Then, the surface of the negative electrode material layer on 10 small discs is wiped off to a thickness of Thk4, and the wiped powder is collected to be the fourth negative electrode material layer powder, and the mass percentage of silicon and the mass percentage of lithium in the fourth negative electrode material layer powder are analyzed using an inductively coupled plasma-optical emission spectrometer (ICP-OES). Then, the negative electrode material layer remaining with a thickness of Thk3 on the 10 small discs is wiped off, and the wiped powder is collected to be the third negative electrode material layer powder, and the mass percentage of silicon and the mass percentage of lithium in the third negative electrode material layer powder are analyzed using an inductively coupled plasma-optical emission spectrometer (ICP-OES). The ICP-OES used is a PE7000DV spectrometer produced by PerkinElmer, USA. The test conditions of ICP-OES are: radio frequency (RF) is 40.68 MHz, RF power is 1300 W, argon secondary pressure is 0.6 MPa, auxiliary gas flow rate is 0.2 L / min, cooling gas flow rate is 15 L / min, and pump speed is 1.5 mL / min.
[0092] Area density test:
[0093] Select the area including the double-sided negative electrode material layer on the pre-lithiation negative electrode plate, and cut 10 pieces with an area of 1540.25mm using a cutting machine. 2Then, the negative electrode material layer on the 10 small discs was wiped off to a thickness of Thk4, and the wiped powder was collected as the fourth negative electrode material layer powder, which was weighed 3 times to obtain the average value M4. Then, the negative electrode material layer with a thickness of Thk3 remaining on the 10 small discs was wiped off, and the wiped powder was collected as the third negative electrode material layer powder, which was weighed 3 times to obtain the average value M3. The surface density CW4 (mg / cm 2 )=(M4×100000) / (2×1540.25), the surface density of the third negative electrode material layer CW3 (mg / cm 2 )=(M3×100000) / (2×1540.25). Wherein, the unit of M4 is g, and the unit of M3 is g.
[0094] First coulombic efficiency test:
[0095] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: charge the lithium-ion battery in the embodiment or comparative example at 25°C at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, stand for 5 minutes, and then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V. The capacity of the above charging process is recorded as C0, and the capacity of the above discharging process is recorded as C1. The first coulomb efficiency is calculated according to the following formula.
[0096] First coulombic efficiency (%) = C1 / C0×100%.
[0097] Cycle performance test:
[0098] The voltage range marked on the factory battery packaging shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, the lithium-ion battery in the embodiment or comparative example is charged and discharged for the first time, charged at a constant current of 0.2C to a cut-off voltage of 4.45V, and then charged at a constant voltage of 4.45V until the current is less than 0.05C, and after standing for 5 minutes, discharged at a constant current of 0.2C to a cut-off voltage of 3.0V, and the discharge capacity of the lithium-ion battery is measured to be A; then, 400 charging and discharging cycles are performed according to the above steps in an environment of 25°C, and the discharge capacity of the lithium-ion battery at the 400th time is measured to be B, and the cycle capacity retention rate is calculated according to the following formula.
[0099] Cycle capacity retention rate (%) = B / A × 100%.
[0100] The larger the value of the cycle capacity retention rate obtained from the test, the better the cycle performance of the lithium-ion battery.
[0101] Energy density test:
[0102] The voltage range marked on the outer packaging of the factory battery shall prevail. For example, when the voltage range marked on the factory battery is 3.0V to 4.45V, the charging cut-off voltage is 4.45V and the discharging cut-off voltage is 3.0V. The specific test steps are: at 25°C, charge the lithium-ion battery in the embodiment or comparative example at a constant current of 0.2C to a cut-off voltage of 4.45V, then charge at a constant voltage of 4.45V until the current is less than 0.05C, let it stand for 5 minutes, then discharge at a constant current of 0.2C to a cut-off voltage of 3.0V, and let it stand for 5 minutes. The energy of the above discharge process is recorded as the discharge energy E. Calculate the volume V (mm) of the lithium-ion battery 3 ) = length × width × height.
[0103] Energy density (Wh / L) = E / V × 10 6 .
[0104] Example 1-1
[0105] <Preparation of lithium-supplementing composite layer>
[0106] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium foil was rolled into a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer. The roller pressure P12 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure.
[0107] Under the condition of ambient temperature of 25℃ and humidity of 1.0%, the interface particle artificial graphite is coated on the surface of the lithium supplement layer by rubbing to form an interface layer, and then roller pressing is performed, the roller pressure P2 is 0.5T / 10mm, the roller pressing temperature T1 is 90℃, and the roller pressing static time t1 is 30min to form a lithium supplement composite layer. Among them, the thickness of the interface layer in the lithium supplement composite layer is 8μm; the thickness of the lithium supplement layer is 0.03mm; along the running direction of the lithium supplement composite layer, the tensile strength of the support layer is 72N / 10mm.
[0108] <Preparation of negative electrode sheet>
[0109] The first negative electrode active material artificial graphite, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 88:2:6:4, deionized water is added as a solvent, and the mixture is stirred and mixed to obtain a first negative electrode slurry, wherein the solid content of the first negative electrode slurry is 28wt%.
[0110] The second negative electrode active material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 98:0.5:1:0.5, and deionized water is added as a solvent, and the mixture is stirred and evenly mixed to obtain a second negative electrode slurry, wherein the solid content of the second negative electrode slurry is 28wt%; the second negative electrode active material includes a silicon-carbon material and artificial graphite, the silicon-carbon material is a silicon-carbon composite material, based on the mass of the silicon-carbon composite material, the mass percentage of silicon element is 50%, and the mass percentage of carbon element is 50%; based on the mass of the second negative electrode active material, the mass percentage of silicon-containing substance is 30%, and the mass percentage of carbon material is 70%.
[0111] The first negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12 μm, and dried at 90°C to obtain a negative electrode sheet coated with the first negative electrode material layer on one side; then the second negative electrode slurry is evenly coated on the surface of the first negative electrode material layer away from the negative electrode current collector copper foil, and dried at 90°C to obtain a negative electrode sheet coated with the first negative electrode material layer and the second negative electrode material layer on one side in sequence. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet. Dry under vacuum conditions at 90°C for 1 hour, and then after cold pressing, cutting and slitting, a negative electrode sheet with a specification of 51mm×44.2mm is obtained. Among them, the surface density of the first negative electrode material layer is 5.94mg / cm 2 The surface density of the second negative electrode material layer is 2.93 mg / cm 2 The compaction density of the cold pressing process is 1.65g / cm 3 Based on the mass of the first negative electrode material layer, the mass percentage of silicon in the first negative electrode material layer is WSi1%, based on the mass of the second negative electrode material layer, the mass percentage of silicon in the second negative electrode material layer is WSi2%, WSi1=0, WSi2=14.7, WSi2>WSi1.
[0112] <Preparation of pre-lithiated negative electrode sheet>
[0113] The prepared negative electrode plate is dried until the water content is ≤500ppm; under the conditions of ambient temperature of 90°C and humidity of 1.0%, the prepared lithium-replenishing composite layer is laminated to the prepared negative electrode plate so that the interface layer is in contact with the second negative electrode material layer, and a pre-lithiation treatment is performed, the interface pressure P3 between the interface layer and the second negative electrode material layer is 0.6MPa, the lamination time t2 between the interface layer and the second negative electrode material layer is 20h, and the lamination temperature T2 between the interface layer and the second negative electrode material layer is 90°C. After the pre-lithiation treatment is completed, the lithium-replenishing composite layer and the negative electrode plate are peeled off to form a pre-lithiation negative electrode plate.
[0114] <Preparation of positive electrode sheet>
[0115] The positive electrode active material lithium cobalt oxide (LiCoO2), the positive electrode conductive agent acetylene black, and the positive electrode binder polyvinylidene fluoride (PVDF) are mixed in a weight ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent, and the mixture is stirred and mixed to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 75wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 12μm, and dried at 110°C to obtain a positive electrode sheet coated with a positive electrode material layer on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode material layer on both sides. Dry under vacuum conditions at 110°C for 1h, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 48mm×41.2mm is obtained. Among them, the surface density of the positive electrode material layer is 19.0mg / cm 2 The compaction density of the cold pressing process is 4.15g / cm 3 .
[0116] <Preparation of Electrolyte>
[0117] In an argon atmosphere glove box with a water content of less than 10ppm, ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and ethyl propionate (EP) were mixed in a weight ratio of 3:1:3:3 to obtain a base solvent, and then lithium salt lithium hexafluorophosphate (LiPF6) was added and mixed evenly to obtain an electrolyte. Based on the mass of the electrolyte, the mass percentage of lithium salt LiPF6 was 12.5%, and the remainder was the base solvent.
[0118] <Preparation of Separator>
[0119] A porous polypropylene film with a thickness of 5 μm (provided by Celgard Company) was used as a separator.
[0120] <Preparation of lithium-ion batteries>
[0121] The prepared positive electrode sheet, separator, pre-lithiated negative electrode sheet and separator are stacked in order, so that the separator is placed between the positive electrode sheet and the pre-lithiated negative electrode sheet to play an isolating role, and the electrode assembly is wound. After welding the pole ear, the electrode assembly is placed in an aluminum plastic film packaging bag, placed in an 85°C vacuum oven for 12 hours to remove moisture, and the electrolyte is injected. After vacuum packaging, standing, formation (charging to 3.5V at a constant current of 0.02C, and then charging to 3.9V at a constant current of 0.1C), degassing, trimming, and capacity processing steps, a lithium-ion battery is obtained.
[0122] Example 1-2 to Example 1-9
[0123] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as Example 1-1.
[0124] Example 2-1 to Example 2-8
[0125] Except for adjusting the surface density of the first negative electrode material layer and / or the second negative electrode material layer by adjusting the coating amount of the first negative electrode slurry and / or the coating amount of the second negative electrode slurry so that the surface density of the third negative electrode material layer and / or the fourth negative electrode material layer is as shown in Table 2, the rest is the same as Examples 1-3.
[0126] Example 3-1
[0127] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 1-3.
[0128] Example 3-2
[0129] Except for preparing the lithium-replenishing composite layer according to the following method, the rest is the same as Example 1-3.
[0130] <Preparation of lithium-supplementing composite layer>
[0131] Under the conditions of ambient temperature of 25°C and humidity of 1.0%, the lithium foil was rolled into a copper foil support layer with a thickness of 14 μm to form a lithium supplement layer. The roller pressure P12 was 1.5T / 10mm to obtain a lithium supplement layer / support layer composite structure.
[0132] Under the condition of ambient temperature of 25℃ and humidity of 1.0%, artificial graphite and acetylene black are first mixed evenly to obtain interface particles, and then the interface particles are coated on the surface of the lithium replenishment layer by rubbing to form an interface layer, and then rolled, the roller pressure P2 is 0.5T / 10mm, the rolling temperature T1 is 90℃, and the rolling standing time t1 is 30min to form a lithium replenishment composite layer. Among them, based on the mass of the interface particles, the mass percentage of lithium insertion material is 80%, and the mass percentage of the conductive agent is 20%; the thickness of the interface layer in the lithium replenishment composite layer is 8μm; the thickness of the lithium replenishment layer is 0.03mm; along the running direction of the lithium replenishment composite layer, the tensile strength of the support layer is 72N / 10mm.
[0133] Example 3-3 to Example 3-5
[0134] Except for adjusting the relevant preparation parameters according to Table 3, the rest is the same as Example 3-2.
[0135] Comparative Example 1
[0136] Except for preparing the negative electrode sheet according to the following method, the rest is the same as Example 1-1.
[0137] <Preparation of negative electrode sheet>
[0138] After mixing the negative electrode active material, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder lithium carboxymethyl cellulose in a weight ratio of 89:2:6:3, deionized water is added as a solvent, and the mixture is stirred to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 28wt%; the negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12μm, and dried at 90°C to obtain a negative electrode sheet coated with a negative electrode material layer on one side. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode material layer on both sides. Dry under vacuum conditions at 90°C for 1h, and then after cold pressing, cutting, and slitting, a negative electrode sheet with a specification of 51mm×44.2mm is obtained. The negative electrode active material includes silicon-carbon material and artificial graphite. The silicon-carbon material is a silicon-carbon composite material. Based on the mass of the silicon-carbon composite material, the mass percentage of silicon element is 50%, and the mass percentage of carbon element is 50%; based on the mass of the negative electrode active material, the mass percentage of silicon-containing substance is 10%, and the mass percentage of carbon material is 90%; the surface density of the negative electrode material layer is 8.97 mg / cm 2 The compaction density of the cold pressing process is 1.65g / cm 3 .
[0139] Comparative Example 2
[0140] Except for preparing the negative electrode sheet according to the following method, the rest is the same as Example 1-3.
[0141] <Preparation of negative electrode sheet>
[0142] A first negative electrode active material, a negative electrode conductive agent acetylene black, a negative electrode binder styrene-butadiene rubber (SBR), and a negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 88:2:6:4, deionized water is added as a solvent, and the mixture is stirred and mixed to obtain a first negative electrode slurry, wherein the solid content of the first negative electrode slurry is 28wt%; the first negative electrode active material includes a silicon-carbon material and artificial graphite, the silicon-carbon material is a silicon-carbon composite material, based on the mass of the silicon-carbon composite material, the mass percentage of silicon element is 50%, and the mass percentage of carbon element is 50%; based on the mass of the first negative electrode active material, the mass percentage of silicon-containing substance is 15%, and the mass percentage of carbon material is 85%.
[0143] The second negative electrode active material artificial graphite, the negative electrode conductive agent acetylene black, the negative electrode binder styrene butadiene rubber (SBR), and the negative electrode binder lithium carboxymethyl cellulose are mixed in a weight ratio of 91:2:4.5:2.5, deionized water is added as a solvent, and the mixture is stirred and mixed to obtain a second negative electrode slurry, wherein the solid content of the second negative electrode slurry is 28wt%.
[0144] The first negative electrode slurry is evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 12 μm, and dried at 90°C to obtain a negative electrode sheet coated with the first negative electrode material layer on one side; then the second negative electrode slurry is evenly coated on the surface of the first negative electrode material layer away from the negative electrode current collector copper foil, and dried at 90°C to obtain a negative electrode sheet coated with the first negative electrode material layer and the second negative electrode material layer in sequence on one side. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet. Dry under vacuum conditions at 90°C for 1 hour, and then after cold pressing, cutting and slitting, a negative electrode sheet with a specification of 51 mm × 44.2 mm is obtained. Among them, the surface density of the first negative electrode material layer is 5.98 mg / cm 2 The surface density of the second negative electrode material layer is 2.99 mg / cm 2 The compaction density of the cold pressing process is 1.65g / cm 3 .
[0145] The preparation parameters, electrode performance parameters and electrical performance parameters of each embodiment and comparative example are shown in Tables 1 to 3.
[0146]
[0147]
[0148] From Examples 1-1 to 1-9, Comparative Examples 1 to 2, it can be seen that the pre-lithiated negative electrode plate of the present application is used, the structure of the pre-lithiated negative electrode plate is within the scope of the present application, the mass percentage of silicon in the fourth negative electrode material layer is greater than the mass percentage of silicon in the third negative electrode material layer, and the ratio of the mass percentage of lithium in the fourth negative electrode material layer to the mass percentage of silicon is within the scope of the present application, and the prepared lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium-ion battery can be improved. The structure of the pre-lithiated negative electrode plate of Comparative Example 1 is not within the scope of the present application, and the prepared lithium-ion battery has a lower first coulombic efficiency, cycle capacity retention rate and energy density. In Comparative Example 2, the mass percentage of silicon in the third negative electrode material layer is greater than the mass percentage of silicon in the fourth negative electrode material layer, and the prepared lithium-ion battery has a lower first coulombic efficiency, cycle capacity retention rate and energy density.
[0149] The value of the mass percentage of lithium element in the fourth negative electrode material layer and its ratio to the mass percentage of lithium element in the third negative electrode material layer will affect the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium ion battery. It can be seen from Examples 1-1 to 1-9 that the value of the mass percentage of lithium element in the fourth negative electrode material layer and its ratio to the mass percentage of lithium element in the third negative electrode material layer are within the scope of the present application, and the prepared lithium ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium ion battery can be improved.
[0150] The mass percentage of silicon in the fourth negative electrode material layer will affect the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-1 to 1-9 that the mass percentage of silicon in the fourth negative electrode material layer is within the scope of this application, and the prepared lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium-ion battery can be improved.
[0151] The mass percentage of silicon-containing substances in the second negative electrode active material will affect the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-3, 1-6 to 1-9 that the mass percentage of silicon-containing substances in the second negative electrode active material is within the scope of this application, and the prepared lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that it can improve the first coulombic efficiency of the lithium-ion battery, reduce the cycle capacity attenuation, and improve the energy density of the lithium-ion battery. In Examples 1-3, 1-6 to 1-9, the mass percentage of the second negative electrode active material remains unchanged. As the mass percentage of silicon-containing substances in the second negative electrode active material decreases, under the same lithium replenishment conditions, the amount of lithium replenishment decreases. The first coulombic efficiency of the lithium-ion battery is affected by the mass percentage of silicon-containing substances and the amount of lithium replenishment. The first coulombic efficiency of the lithium-ion battery first increases and then decreases.
[0152] The difference between the mass percentage of the second negative electrode active material and the mass percentage of the first negative electrode active material will affect the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-1 to 1-5 that the difference between the mass percentage of the second negative electrode active material and the mass percentage of the first negative electrode active material is within the scope of this application, and the prepared lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that it can improve the first coulombic efficiency of the lithium-ion battery, reduce the cycle capacity attenuation, and improve the energy density of the lithium-ion battery. In Examples 1-1 to 1-5, the mass percentage of the silicon-containing substance in the second negative electrode active material remains unchanged, and the mass percentage of the second negative electrode active material decreases, which will affect the kinetic performance of the lithium-ion battery. Under the same lithium replenishment conditions, the amount of lithium replenishment decreases, and the first coulombic efficiency of the lithium-ion battery decreases.
[0153] Table 2
[0154]
[0155] The surface density of the third negative electrode material layer and the ratio of the surface density of the fourth negative electrode material layer to the surface density of the third negative electrode material layer will affect the first coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-3 and 2-1 to 2-8 that the surface density of the third negative electrode material layer and the ratio of the surface density of the fourth negative electrode material layer to the surface density of the third negative electrode material layer are within the scope of this application, and the prepared lithium-ion battery has a higher first coulombic efficiency, cycle capacity retention rate and energy density, indicating that the first coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium-ion battery can be improved.
[0156] In Example 1-3, Example 2-2, and Example 2-1, under the same lithium supplementation conditions, the surface density of the third negative electrode material layer and the fourth negative electrode material layer gradually decreases, and there is a possibility of excessive lithium supplementation, which will affect the cycle performance of the lithium-ion battery, and the cycle capacity retention rate of the lithium-ion battery gradually decreases; in Example 1-3, Example 2-3 to Example 2-5, the surface density of the third negative electrode material layer and the fourth negative electrode material layer gradually increases, and the thickness of the third negative electrode material layer and the fourth negative electrode material layer gradually increases, which will affect the dynamic performance of the lithium-ion battery, and the cycle capacity retention rate of the lithium-ion battery gradually decreases. In Example 1-3, Example 2-6 to Example 2-8, the surface density of the fourth negative electrode material layer increases, and the thickness of the fourth negative electrode material layer increases, which will affect the dynamic performance of the lithium-ion battery, and the cycle capacity retention rate of the lithium-ion battery gradually decreases.
[0157] Table 3
[0158]
[0159]
[0160] The composition of the interface particles will affect the amount of lithium replenishment of the negative electrode active material in the pre-lithiated negative electrode plate, thereby affecting the initial coulombic efficiency, cycle capacity retention rate and energy density of the lithium-ion battery. It can be seen from Examples 1-3 and 3-1 to 3-5 that when the interface particles include lithium-intercalation materials and conductive agents, and the mass percentages of the lithium-intercalation materials and the conductive agents are within the scope of this application, the prepared lithium-ion battery has a higher initial coulombic efficiency, cycle capacity retention rate and energy density, indicating that the initial coulombic efficiency of the lithium-ion battery can be improved, the cycle capacity attenuation can be reduced, and the energy density of the lithium-ion battery can be improved.
[0161] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method or article.
[0162] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0163] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.
Claims
1. A method for preparing a lithium supplement composite layer, comprising the following steps: (1) coating a lithium metal powder slurry on a support layer, drying it, and rolling it to form a lithium supplement layer; or rolling a lithium foil and / or a lithium alloy foil onto a support layer to form a lithium supplement layer; or coating a lithium or lithium alloy molten slurry on a support layer, cooling it, and rolling it to form a lithium supplement layer; wherein the rolling pressure P1 is 0.2T / 10mm to 1.8T / 10mm; (2) coating the interface particles on the surface of the lithium replenishing layer to form an interface layer, and then rolling the layer, wherein the rolling pressure P2 is 0.2T / 10mm to 1.8T / 10mm, the rolling temperature T1 is 20°C to 180°C, and the rolling standing time t1 is 5min to 60min, to form a lithium replenishing composite layer.
2. The preparation method according to claim 1, wherein The lithium supplement composite layer comprises the support layer, the lithium supplement layer and the interface layer, and the lithium supplement layer is arranged between the support layer and the interface layer; The interface layer includes the interface particles, the interface particles include at least one of a conductive agent or a lithium-intercalated material, the conductive agent includes at least one of conductive carbon black, carbon fiber, graphene or carbon nanotubes, and the lithium-intercalated material includes at least one of artificial graphite, natural graphite, hard carbon, silicon-carbon material, silicon-oxygen material, lithium titanate, tin or tin-copper alloy; The lithium supplement layer includes at least one of lithium foil and lithium alloy foil.
3. The preparation method according to claim 2, wherein The interface particles include lithium intercalation material and a conductive agent. Based on the mass of the interface particles, the mass percentage of the lithium intercalation material is 80% to 99%, and the mass percentage of the conductive agent is 1% to 20%.
4. A lithium supplementation method comprising the following steps: Drying a negative electrode sheet, wherein the negative electrode sheet comprises a negative electrode current collector, a first negative electrode material layer and a second negative electrode material layer, wherein along a thickness direction of the negative electrode sheet, the first negative electrode material layer is disposed between the negative electrode current collector and the second negative electrode material layer, and the second negative electrode material layer comprises a silicon-containing substance; Based on the mass of the first negative electrode material layer, the mass percentage of silicon in the first negative electrode material layer is WSi1%, and based on the mass of the second negative electrode material layer, the mass percentage of silicon in the second negative electrode material layer is WSi2%, WSi2>WSi1; The lithium-replenishing composite layer prepared by the preparation method according to any one of claims 1 to 3 is laminated to the negative electrode plate so that the interface layer is in contact with the second negative electrode material layer, and a pre-lithiation treatment is performed. After the pre-lithiation treatment is completed, the lithium-replenishing composite layer is peeled off from the negative electrode plate to form a pre-lithiation negative electrode plate.
5. The lithium supplementation method according to claim 4, wherein: During the pre-lithiation treatment, the interface pressure P3 between the interface layer and the second negative electrode material layer is 0.1 MPa to 2 MPa, the bonding time t2 between the interface layer and the second negative electrode material layer is 0.5h to 72h, and the bonding temperature T2 between the interface layer and the second negative electrode material layer is 50°C to 180°C.
6. A pre-lithiated negative electrode sheet prepared by the lithium replenishment method according to claim 4 or 5, the negative electrode sheet comprising a negative electrode current collector, a third negative electrode material layer and a fourth negative electrode material layer, along the thickness direction of the negative electrode sheet, the third negative electrode material layer is arranged between the negative electrode current collector and the fourth negative electrode material layer, the third negative electrode material layer comprises a first negative electrode active material, the fourth negative electrode material layer comprises a second negative electrode active material, and the second negative electrode active material comprises a silicon-containing substance; Based on the mass of the third negative electrode material layer, the mass percentage of silicon element in the third negative electrode material layer is WSi3%, based on the mass of the fourth negative electrode material layer, the mass percentage of silicon element in the fourth negative electrode material layer is WSi4%, the mass percentage of lithium element in the fourth negative electrode material layer is WLi4%, WSi4>WSi3, 1.5%≤WLi4 / WSi4≤44.4%.
7. The pre-lithiated negative electrode sheet according to claim 6, wherein: Based on the mass of the third negative electrode material layer, the mass percentage of lithium element in the third negative electrode material layer is WLi3%, 1.1≤WLi4 / WLi3≤4.8, 0.2≤WLi4≤4.
4.
8. The pre-lithiated negative electrode sheet according to claim 6, wherein: 0.9≤WSi4≤43.
5.
9. The pre-lithiated negative electrode sheet according to claim 6, wherein: Based on the mass of the second negative electrode active material, the mass percentage of the silicon-containing substance is S2%, 2≤S2≤100.
10. The pre-lithiated negative electrode sheet according to claim 6, wherein: Based on the mass of the third negative electrode material layer, the mass percentage of the first negative electrode active material is H1%, based on the mass of the fourth negative electrode material layer, the mass percentage of the second negative electrode active material is H2%, and 0.1≤H2-H1≤10.
11. The pre-lithiated negative electrode sheet according to claim 6, wherein: The surface density of the third negative electrode material layer is CW3 mg / cm 2 The surface density of the fourth negative electrode material layer is CW4 mg / cm 2 , 0.8≤CW3≤50, 0.25≤CW4 / CW3≤1.
12. The pre-lithiated negative electrode plate according to claim 6, which satisfies at least one of the following characteristics: (1) Based on the mass of the third negative electrode material layer, the mass percentage of lithium element in the third negative electrode material layer is WLi3%, 1.4≤WLi4 / WLi3≤3.3; (2) Based on the mass of the third negative electrode material layer, the mass percentage of the first negative electrode active material is H1%, based on the mass of the fourth negative electrode material layer, the mass percentage of the second negative electrode active material is H2%, 1≤H2-H1≤5; (3) The surface density of the third negative electrode material layer is CW3 mg / cm 2 , 1.0≤CW3≤13.0; (4) The silicon-containing material includes at least one of a silicon-carbon material or a silicon-oxygen material. 13 . A secondary battery comprising the pre-lithiated negative electrode sheet according to claim 6 . 14 . An electronic device comprising the secondary battery according to claim 13 .
Citation Information
Patent Citations
Preparation method for lithium ion supercapacitor taking stabilized lithium metal powder as negative electrode
CN106449140A
Electrochemical device and electronic device
CN117117111A
Method for improving first-cycle coulombic efficiency of silicon negative electrode through pre-lithiation
CN117239063A
Negative electrode plate, and electrochemical device and electronic device comprising negative electrode plate
WO2024050813A1
Cited By
Negative plate, battery and electric equipment
CN122455676A